2021
DOI: 10.1016/j.envres.2021.111182
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological conditions are heterogeneous factors for COVID-19 risk in China

Abstract: Whether meteorological factors influence COVID-19 transmission is an issue of major public health concern, but available evidence remains unclear and limited for several reasons, including the use of report date which can lag date of symptom onset by a considerable period. We aimed to generate reliable and robust evidence of this relationship based on date of onset of symptoms. We evaluated important meteorological factors associated with daily COVID-19 counts and effective reproduction number ( R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Our work can be compared to other previously published studies on seasonality and COVID-19, among which are also some focused on non-temperate areas that failed to show an association with temperature changes ( Kumar, 2020 ; Xiao et al, 2021 ; Byun et al, 2021 ). Bukhari et al demonstrated that 90% of SARS-CoV-2 infections during the early months of the pandemic occurred at relatively cold temperatures, between 5 and 10 °C ( Bukhari and Jameel, 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…Our work can be compared to other previously published studies on seasonality and COVID-19, among which are also some focused on non-temperate areas that failed to show an association with temperature changes ( Kumar, 2020 ; Xiao et al, 2021 ; Byun et al, 2021 ). Bukhari et al demonstrated that 90% of SARS-CoV-2 infections during the early months of the pandemic occurred at relatively cold temperatures, between 5 and 10 °C ( Bukhari and Jameel, 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…In the current study, we also found that humidity was negatively related to daily COVID-19 cases and was a stable driver of SARS-CoV-2 transmission, consistent with the above studies. However, the observed relationship between COVID-19 cases and humidity has not always been consistent; for example, this relationship was found to be heterogeneous between different cities in China [ 12 ], and in a global study of 190 countries an inverse J-shaped relationship was found between relative humidity and COVID-19 incidence, in which risk was greatest at 72% relative humidity [ 7 ]. It is likely that a range of other factors influences the relationship between transmission of SARS-CoV-2 and humidity, particularly climatic zone.…”
Section: Discussionmentioning
confidence: 99%
“…The same method used in previous studies was applied to investigate the relationship between reported cases of COVID-19 and weather variables [ 4 , 8 , 9 , 12 , 20 ]. A Spearman correlation (ρ) coefficient matrix was first calculated to avoid multicollinearity among the predictor variables, and a 14-day exponential moving average (EMA) was used to represent the effects of weather factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its effects, now widely documented by spatially distributed data available at different scales ( Sheng et al, 2021 ), show that the variability in both incidence and mortality is relevant between continents, across countries, and even between geographical regions within each nation ( Saez et al, 2020 ). More than a year after the declaration of a pandemic emergency by the World Health Organization, the scientific literature has been enriched by studies and research that attempt to explain these differences by considering, among the others, geographical and environmental variables ( Dettori et al, 2020 ; Saez et al, 2020 ; Xiao et al, 2021 ), as well as demographic and socio-economic factors ( Abtahi et al, 2021 ; Deiana et al, 2021 ; Drefahl et al, 2020 ; Ehlert, 2021 ; Gangemi et al, 2020 ). The understanding of these factors, whose relative weight varies according to the specific reference context, is essential for the implementation of territorial policies and strategies of urban spaces’ management oriented to risk mitigation and improvement of the quality of life with specific attention to the various components of public health.…”
Section: Introductionmentioning
confidence: 99%